Observation of high nonlinearity in Bi doped BixIn35-xSe65 thin films with annealing - P. Priyadarshini (Nature Portfolio, 2021)
Abstract The present work demonstrates the impact of thermal annealing on the structural, linear, and non-linear optical characteristics of thermally evaporated BixIn35-xSe65 (x = 0, 5, 10, 15 at%) thin films. The prominent crystalline phases have been developed for all annealed films at 450 °C whereas the films remain amorphous at 350 °C annealing. The XRD and Raman analysis showed the phase transformation of Bi-doped films and new Bi2Se3 phases developed upon annealing at 450 °C. The phase transformation induced change increased the linear and nonlinear properties with great extent as seen from the UV–visible optical studies. The direct and indirect optical bandgaps decreased with annealing temperature and also with Bi % content due to the formation of surface dangling bonds near the crystallite sites. The static linear refractive index and high-frequency dielectric constants were increased with annealing. The third-order non-linear susceptibility and non-linear refractive index were found to be greatly influenced by annealing temperature and increased with bismuth content. The FESEM micrographs also showed the phase transformation and EDX analysis showed the composition. The results obtained from the materials showed the potentiality to be useful for photovoltaic and optoelectronic applications.